Proposed Training Program For Developing Non-verbal Communication In Children With Autism Spectrum Disorder - Djalab, Mohammed Salah; Belkhir, Hanane (University of Eloued جامعة الوادي, 2024)
Abstract: The study presents a training program designed to enhance non-verbal communication skills in children with autism spectrum disorder (ASD) and evaluates its effectiveness. A sample of five children with ASD from the Al-Mann and Salwa Center for Special Needs in El Bayadh, El Oued province, participated in the study. Using a semi-experimental one-group pretest-posttest design, the Childhood Autism Rating Scale (CARS) and the Language Communication Rating Scale were administered after validation and reliability checks. After the implementation of the training program, statistical analysis using SPSS revealed significant improvements: _ Significant improvements were observed in recognition and understanding skills. _ Expression skills showed notable enhancement. _ Naming skills also demonstrated significant progress.There are statistically significant differences between the pretest and posttest results in recognition and understanding skills, favoring the posttest results. _ There are statistically significant differences between the pretest and posttest results in expression skills, favoring the posttest results. _ There are statistically significant differences between the pretest and posttest results in naming skills, favoring the posttest results. Therefore, the study proved the effectiveness of the proposed training program in developing non-verbal communication among children with ASD.
Keywords: Autism Spectrum Disorder; Non-Verbal Communication; Training Program